2010
DOI: 10.1016/j.yqres.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Local-Scale Spatial Variability of Soil Organic Carbon and its Stock in the Hilly Area of the Loess Plateau, China

Abstract: a b s t r a c t a r t i c l e i n f oSoil organic carbon (SOC) is one of the key components for assessing soil quality. Meanwhile, the changes in the stocks SOC may have large potential impact on global climate. It is increasingly important to estimate the SOC stock precisely and to investigate its variability. In this study, Yangjuangou watershed was selected to investigate the SOC distribution under different land uses. We found that SOC concentration decreased with increasing soil depth under all land uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 28 publications
7
54
1
2
Order By: Relevance
“…Spiraea pubescens and Hippophae rhamnoide are the major shrub species. Details of the study site were also documented by Liu et al (2012) and Wang et al (2010).…”
Section: Study Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spiraea pubescens and Hippophae rhamnoide are the major shrub species. Details of the study site were also documented by Liu et al (2012) and Wang et al (2010).…”
Section: Study Site Descriptionmentioning
confidence: 99%
“…The many native and cultivated plant species distributed in a mosaic fashion in the Yangjuangou catchment all have different morphological characteristics (Hu et al, 2010), soil water use efficiencies , soil nutrient and conservation effects (Fu et al, 2009;Wang et al, 2010), and soil moisture inputs. Understanding of these factors provides the basis for predicting the hydrological characteristics of hill slopes, catchments and other topographic features occupied by combinations of these plant species.…”
Section: Differences In Soil Moisture and Infiltration Among Land Covmentioning
confidence: 99%
“…In Mediterranean areas, the elements that affect soil carbon (C) variability are mainly climate (Wang et al, 2010), land use (Lozano-García and Parras-Alcántara, 2013b), management , 2014a, slope and altitude (Hontoria et al, 2004;Lozano-García and ParrasAlcántara, 2014), tillage intensity and no-till duration (Conant et al, 2007). Of all these factors, soil management is the best tool for climate change mitigation and adaptation (Lal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated that after 20 years of afforestation the total amount of soil C increased by 23% in the first 10 cm of soil in humid Mediterranean conditions (Galdo et al, 2003). Wang et al indicated that it is only in 5 cm depth of soil surface that SOC contents are significant for different land covers at semi-arid climate of the hilly Loess Plateau of China (Wang et al, 2010). Reductions of 10% to 40% of the soil C in cultivated soils compared with the non-cultivated soils have been reported in China with the highest losses from the semi-arid and subhumid areas (Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%